2014
DOI: 10.1007/s13365-014-0243-9
|View full text |Cite
|
Sign up to set email alerts
|

Complement and HIV-I infection/HIV-associated neurocognitive disorders

Abstract: The various neurological complications associated with HIV-1 infection, specifically HIV-associated neurocognitive disorders (HAND) persist as a major public health burden worldwide. Despite the widespread use of anti-retroviral therapy, the prevalence of HAND is significantly high. HAND results from the direct effects of an HIV-1 infection as well as secondary effects of HIV-1-induced immune reaction and inflammatory response. Complement, a critical mediator of innate and acquired immunity, plays important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 131 publications
(161 reference statements)
0
32
0
2
Order By: Relevance
“…It is confirmed that HIV-1 virions isolated from infected individuals have accumulated C3 on their surface, a signal of the initiation of complement reactions, but HIV-1 virions are still very resistant to complement mediated killing, which is a different phenomenon of humoral immune responses induced from the most invaded pathogens [32]. More and more experimental and clinical evidences indicate that MAC pores supposed to be seen on the surface of invaded pathogen are not effectively formed in the case of HIV infection, leading to the escape of virus and all over spreading through the blood and lymph systems in HIV patients [53,54].…”
Section: Critical Role Of Fh In Pathogenesis Of Several Dreadful Disementioning
confidence: 99%
See 1 more Smart Citation
“…It is confirmed that HIV-1 virions isolated from infected individuals have accumulated C3 on their surface, a signal of the initiation of complement reactions, but HIV-1 virions are still very resistant to complement mediated killing, which is a different phenomenon of humoral immune responses induced from the most invaded pathogens [32]. More and more experimental and clinical evidences indicate that MAC pores supposed to be seen on the surface of invaded pathogen are not effectively formed in the case of HIV infection, leading to the escape of virus and all over spreading through the blood and lymph systems in HIV patients [53,54].…”
Section: Critical Role Of Fh In Pathogenesis Of Several Dreadful Disementioning
confidence: 99%
“…The complement-mediated lysis could be further enhanced through the addition of a blocking antibody against CD55; however, FH binding was shown to be responsible for most of the resistance mechanism in both cases. It has been confirmed that resistance to human complement can be completely overcome if Decay accelerating factor (DAF)/CD55 and FH are set out of function [32, 53,54].…”
Section: Critical Role Of Fh In Pathogenesis Of Several Dreadful Disementioning
confidence: 99%
“…Natural killer cell activation is present in the setting of HIV and does not normalize despite virologic suppression during cART (Lichtfuss et al, 2012). Additionally, activation of the complement system has been recognized since the early years of the HIV epidemic (Liu et al, 2014, Senaldi et al, 1990). It is possible that the complement system plays a role in HIV neuropathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Complement is activated early in HIV infection via a variety of mechanisms, but it fails to eradicate HIV from infected cells and from the circulation due to the presence of complement regulators within the HIV-1 envelope and on infected cells (Liu et al 2014). Instead, HIV uses complement activation to spread and enhance systemic infection (Liu et al 2014). The role of complement in the neuropathogenesis of HIV is less well understood.…”
Section: Introductionmentioning
confidence: 99%
“…The role of complement in the neuropathogenesis of HIV is less well understood. Local HIV infection induces C3 production in neuronal and glial cell lines incubated with HIV and in parallel downregulates normal complement inhibitor proteins (CD59) (Stephan et al 2012; Liu et al 2014). In a simian immunodeficiency virus (SIV) model, cerebral synthesis of C1q and C3 was upregulated compared to controls and deposited on neuronal membranes (Speth et al 2004).…”
Section: Introductionmentioning
confidence: 99%